PENGARUH PEMBERIAN SUSU KEDELAI TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA DI PMB LINAH JULIANAH TAHUN 2023 - Burhan, Dela Namirah Zasqiah (Journal of Midwifery Tiara Bunda, 2024)
Anemia is a disease caused by a lack of blood due to hemoglobin levels below normal, which is below 11gr/dl during the second and third trimesters. The causes of anemia in pregnant women are iron deficiency and acute bleeding or the interaction of both. The impact of iron deficiency in pregnant women can cause fetal growth disorders, both fetal body cells and fetal brain cells. Anemia can also cause fetal death in the womb, abortion, congenital defects and Low Birth Weight. According to WHO data in 2017, the incidence of anemia in pregnant women globally was 28-36 million people. The highest anemia in the world is in South Asia, Central Asia and West Africa. The number of anemia in Asia is 12-22 million people, and the lowest is in Oceania or the Pacific Ocean region around 100-200 people. While anemia in pregnant women in Indonesia is still relatively high at 37.1%. The nutrients needed in the formation of hemoglobin are protein. Soy milk is one source of protein from processed soybean extraction. Soy milk which is rich in protein provides reserves stored in the liver, spleen and bone marrow to provide protein needs, especially the formation of hemoglobin. The design used in this study is an experimental study with a Pre-experimental design with a One Group pretest and posttest design. The population in this study were all pregnant women at PMB Linah Julianah, S.Tr.Keb who underwent laboratory checks and their hemoglobin test results were low or below normal, with a sample size of 13 people, with a total sampling technique. Bivariate analysis in the study used the Wilcoxon test. The results of the study obtained a p-value of 0.000 <0.05, so Ha was accepted, meaning there was a difference in hemoglobin in pregnant women before and after being given soy milk, meaning there was an effect of soy milk on increasing hemoglobin levels in pregnant women at PMB Linah Julianah, S.Tr.Keb in 2024. It is hoped that giving soy milk can be used as a complementary therapy to increase hemoglobin levels in pregnant women.